Prehospital antibiotics in the ambulance for sepsis: a multicentre, open label, randomised trial. Issue 1 (January 2018) - Alam, Nadia; Oskam, Erick; Stassen, Patricia M; Exter, Pieternel van; van de Ven, Peter M; Haak, Harm R; Holleman, Frits; Zanten, Arthur van; Leeuwen-Nguyen, Hien van; Bon, Victor; Duineveld, Bart A M; Nannan Panday, Rishi S; et al.
Summary: Background: Emergency medical services (EMS) personnel have already made substantial contributions to improving care for patients with time-dependent illnesses, such as trauma and myocardial infarction. Patients with sepsis could also benefit from timely prehospital care. Methods: After training EMS personnel in recognising sepsis, we did a randomised controlled open-label trial in ten large regional ambulance services serving 34 secondary and tertiary care hospitals in the Netherlands. We compared the effects of early administration of antibiotics in the ambulance with usual care. Eligible patients were randomly assigned (1:1) using block-randomisation with blocks of size 4 to the intervention (open-label intravenous ceftriaxone 2000 mg in addition to usual care) or usual care (fluid resuscitation and supplementary oxygen). Randomisation was stratified per region. The primary outcome was all-cause mortality at 28 days and analysis was by intention to treat. To assess the effect of training, we determined the average time to antibiotics (TTA) in the emergency department and recognition of sepsis by EMS personnel before and after training. The trial is registered atClinicalTrials.gov, numberNCT01988428 . Findings: 2698 patients were enrolled between June 30, 2014, and June 26, 2016. 2672 patients were included in the intention-to-treat analysis: 1535 in the intervention group and 1137 in the usual care group. The intervention group received antibiotics a median of 26 min (IQR 19–34) before arriving at the emergency department. In the usual care group, median TTA after arriving at the emergency department was 70 min (IQR 36–128), compared with 93 min (IQR 39–140) before EMS personnel training (p=0·142). At day 28, 120 (8%) patients had died in the intervention group and 93 (8%) had died in the usual care group (relative risk 0·95, 95% CI 0·74–1·24). 102 (7%) patients in the intervention group and 119 (10%) in the usual care group were re-admitted to hospital within 28 days (p=0·0004). Seven mild allergic reactions occurred, none of which could be attributed to ceftriaxone. Interpretation: In patients with varying severity of sepsis, EMS personnel training improved early recognition and care in the whole acute care chain. However, giving antibiotics in the ambulance did not lead to improved survival, regardless of illness severity. Funding: The NutsOhra Foundation, Netherlands Society of Internal Medicine (NIV).